2003
DOI: 10.1623/hysj.48.4.637.51412
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in flood and low-flow regimes in New Zealand due to interdecadal climate variations

Abstract: Thirty-one of the longest available streamflow records for New Zealand were analysed to see whether shifts in flood and low-flow regime occurred in 1977/1978 corresponding to a shift in phase of the Interdecadal Pacific Oscillation. Annual peak flows, and annual minimum flows averaged over 28 days, for two periods, 1947-1977 and 1978-1999, were compared using box plots and statistical tests. The plots and the tests show that a decrease of flood size has occurred since 1978 in the Bay of Plenty region of the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…77 McKerchar and Henderson (2003) found changes in several hydrological variables in New Zealand which were consistent with changes in the Interdecadal Pacific Oscillation. Jacobeit et al (2006) determined large-scale CP for historical flood events with the help of Reanalysis data.…”
Section: T Petrow Et Al: Changes In the Flood Hazard In Germanymentioning
confidence: 67%
“…77 McKerchar and Henderson (2003) found changes in several hydrological variables in New Zealand which were consistent with changes in the Interdecadal Pacific Oscillation. Jacobeit et al (2006) determined large-scale CP for historical flood events with the help of Reanalysis data.…”
Section: T Petrow Et Al: Changes In the Flood Hazard In Germanymentioning
confidence: 67%
“…Mantua et al (1997) found that the IPO affects coastal sea and continental surface air temperature, as well as streamflow in major west-coast river systems, from Alaska to California. On a smaller spatial scale, McKerchar and Henderson (2003) investigated the association between the shift in flood and low-flow regime and the shift in phase of the IPO. This kind of shift in ENSO behaviour could account for the trend identified for some of the river basins.…”
Section: Recent Versus Earlier Tendenciesmentioning
confidence: 99%
“…Most studies (with some exceptions, such as Mitosek, 1995) have only analysed a few rivers, or at most a region or a single country (e.g. McKerchar & Henderson, 2003;Burn et al, 2004;Callède et al, 2004;Lindström & Bergström, 2004;Xiong & Guo, 2004). In contrast, a global-scale assessment of trends in annual maximum streamflow is presented herein.…”
Section: Introductionmentioning
confidence: 99%